2012
DOI: 10.1177/0278364912455366
|View full text |Cite
|
Sign up to set email alerts
|

The role of roles: Physical cooperation between humans and robots

Abstract: Since strict separation of working spaces of humans and robots experiences a softening due to recent robotics research achievements, close interaction of humans and robots comes rapidly into reach. In this context, physical human-robot interaction raises a number of questions regarding a desired intuitive robot behavior. The continuous bilateral information and energy exchange requires an appropriate continuous robot feedback. Investigating a cooperative manipulation task, the desired behavior is a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
191
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(193 citation statements)
references
References 48 publications
1
191
0
1
Order By: Relevance
“…But due to reasons of efficiency and productivity of the whole team the test subjects started to switch these roles during the experiment. This is also a well-known fact within this research field as several studies have revealed that a continuous dynamic role allocation is superior over a constant role strategy [17]. Regarding to the results of the described experiment this flexibility of role allocation is also a characteristic of humanrobot-teams.…”
Section: Empirical Study On Human-robot-teamssupporting
confidence: 60%
“…But due to reasons of efficiency and productivity of the whole team the test subjects started to switch these roles during the experiment. This is also a well-known fact within this research field as several studies have revealed that a continuous dynamic role allocation is superior over a constant role strategy [17]. Regarding to the results of the described experiment this flexibility of role allocation is also a characteristic of humanrobot-teams.…”
Section: Empirical Study On Human-robot-teamssupporting
confidence: 60%
“…Interpreting the role adaptation law (14), the robot adjusts its role according to the new role of the human. Specifically, whenever the human interacts with the robot by exerting a force f , the weight R 2 will be updated via (14), until f tracks the optimal control f * .…”
Section: Discussionmentioning
confidence: 99%
“…Risk-sensitive optimal feedback control is proposed in [11], which is the basis of the following two works: in [12], role adaptation is achieved by adaptive attitude design depending on both the disagreement level and environmental situation; and in [13], an adaptation strategy is developed to switch between model-based and model-free predictions in the case of partially known tasks. In [14], a shared plan of human and the robot is given as a desired trajectory of the object configuration and the common goal of the cooperation is known to both agents. In [15], impedance parameters of the human arm are estimated online, and the leader/follower role of robot is switched according to the recognized human intention.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of assistance benefits from goal-oriented robot behavior -in contrast to purely reactive behavior -as shown for example in a cooperative load transport task [17,22]. For simplicity and clarity we focus here on the physical assistance in the redundant degrees of freedom of the task, i.e.…”
Section: Technical Approachmentioning
confidence: 99%
“…Potential methods for decision and blending are proposed in this work. The interaction control layer can be implemented as static role allocation (leader/follower) [17] or dynamic effort sharing strategy [22]. Alternatively, a risk-sensitive optimal feedback control scheme can be applied to generate an intuitive robot force contribution depending on observed human execution variability [21].…”
Section: Problem Settingmentioning
confidence: 99%